Os efeitos da reestruturação operacional sobre a qualidade do trabalho no setor supermercadista brasileiro (1994-2005) - Santos, José Márcio dos (2008)
The commercial section blunts, after the coming of Plano Real, as one of the main segments of the Brazilian economy. In this section is inserted the self-service retail section is inserted, represented in your majority by the supermarkets and hypermarkets. After the opening of the economy and the inflationary stabilization, these establishments were object of intense investments that promoted a restructuring process, sponsored mainly by investments of foreign capital. This allowed the dissemination of new administrative and operational techniques, especially ruled in the technological automation. Such changes promoted several and significant alterations on the job exercised in this companies. In this context, this study intended to analyze the dissemination consequences of this phenomenon on the labour used in the supermarkets and hypermarkets. To reach such objective, quantitative and qualitative analyses were taken about the behavior of the labour. The theoretical approach consisted on Marx s conception of the commercial capital and its derived aspects, as a form of understanding the dynamics of the operation of the commercial section. Besides the bibliographical revision, the methodology constituted in interviews accomplished in retail establishments, use of number-indexes and use of the Indicator of Quality of the Formal Employment (IQEF). As data base was used the ranking of the companies of the self-service retail published by Supermarkets Brazilian Association (ABRAS), and the data of RAIS published by Brazilian s Ministry of Labour and Employment. The obtained result shows two tendencies. First, they indicate the occurrence of a progressive substitution of the manpower for the capital, a phenomenon synthesized by the constant automation and concentration of the section. Second, the remaining labour is subject to the intensification of its functions, taking as a direct consequence the degradation of the conditions of the job in these establishments. That is signaled, mainly, by the wage s reduction and elevation of the labour s change registered in the studied sections.